Prokaryotic expression and characterisation of recombinant M1 protein of an Indian H5N1 avian influenza virus - SYED, ZOHRA; VENKATESH, GOVINDARAJULU; MURUGKAR, HARSHAD V; BEDEKAR, MEGHA KADAM; NAGARAJAN, SHANMUGASUNDARAM; DUBEY, SHIV CHANDRA (The Indian Journal of Animal Sciences, 2012)
The type specific Matrix 1 (M1) protein of an Indian H5N1 avian influenza virus (AIV) was expressed as a histidine- tagged fusion protein in a prokaryotic expression system and characterized. The M1 gene was amplified by reverse transcription PCR using appropriately designed primers and cloned into the expression vector, pET28a (+). The orientation and reading frame of the recombinant expression construct (pET-M1) was confirmed by sequence analysis. The derived amino acid sequence homology between M1 of AIV H5N1 and other reference AIV subtypes was found to be 93.7% to 99.2%. The 33kDA recombinant M1 (rM1) protein was expressed as inclusion body after induction with 1 mM IPTG in E. coli BL21 (DE3)pLysS cells. The protein was purified to near homogeneity by affinity chromatography using Ni- NTA agarose column. The yield of the purified rM1 was found to be 2 mg/100 ml of induced culture. The rM1 was found to react specifically with H1-H15 AIV subtype specific sera in Western blot. The results indicated that the purified rM1 protein could be used as antigen for detection of type specific AIV antibodies by immunoassays.